Chemical Strategies for the Diversification of Landomycins and DEL Target Scaffolds toward the Discovery of New Therapeutics - Maiello, Kathleen (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2026.; Submitted to the Dept. of Chemistry.; Advisor: Clay Bennett.; Committee: Charles Mace, Krishna Kumar, Luke Davis, and Alexei Demchenko.; Keywords: Organic chemistry, Bioengineering, and Chemistry